Current Aspects Of Green Economy And Green Financing In Uzbekistan - Nasiba Khasanova (LPPM STIE KRAKATAU, 2025)
Purpose: This study aims to analyze the organization of green financing mechanisms within the green economy framework, with particular emphasis on the criteria and requirements for selecting and funding green projects. The research also explores how green finance contributes to sustainable development, guided by national strategies such as the “Development Strategy of New Uzbekistan for 2022–2026.” Research Methodology: The study employs a qualitative descriptive approach, integrating document analysis and comparative review of international practices in green economy financing. It examines regulatory frameworks, the role of international financial institutions, and Uzbekistan’s strategic policies on environmental and economic sustainability. Results: Findings reveal that effective green financing depends on well-defined project selection criteria, financial incentives, and institutional collaboration. Uzbekistan’s policy initiatives align with global sustainability goals and emphasize capitalizing ecological activities to achieve economic benefits. International experiences—particularly those of the UN and global financial institutions—highlight the effectiveness of green bonds, carbon credits, and green investment funds in promoting sustainable development. Conclusions: The study concludes that integrating ecological priorities into financial systems enhances both environmental protection and economic resilience. A national green finance strategy is crucial for ensuring long-term growth and compliance with global sustainable development goals. Limitations: The research focuses primarily on policy and institutional perspectives, with limited empirical analysis of local implementation outcomes. Contribution: This study contributes to understanding how green financing frameworks can be adapted in developing countries to balance economic progress with environmental sustainability.